Buckling analysis of tapered piles using non-prismatic beam-column element model. (November 2021) - Wan, Jian-Hong; Liu, Si-Wei; Li, Xue-You; Zhang, Li-Min; Zhao, Hai-Peng
Abstract: Tapered piles have superior benefits over traditional cylindrical piles in resisting axial and lateral loads, being an economical alternative to cylindrical piles. When designing the tapered pile in soft or liquefiable soil, it is necessary to identify its buckling strengths. Notwithstanding, the buckling analysis of tapered piles considering nonlinear pile-soil interactions with geometric imperfections under combined loads has not been well established. This paper presents a non-prismatic beam-column element for nonlinear buckling analysis, considering nonlinear pile-soil interactions, combined external loads, and geometric imperfections, to robustly and efficiently simulate the buckling response of tapered piles. Unlike the discrete-spring stepped element (DSSE) model using an approximate stepwise modeling approach, analytical expressions for considering the axial and flexural rigidity of tapered section members are derived in the proposed element formulations to explicitly model the tapered sections. Several examples of buckling analysis are provided to validate the accuracy and efficiency of the proposed method. Parametric studies are performed to investigate the influences of Young's modulus, taper ratio, initial geometric imperfection, and horizontal load on the buckling behavior of tapered piles with different boundary conditions. The critical buckling load of tapered piles is found to increase with increasing Young's modulus and decreasing initial geometric imperfection and horizontal load. An optimal taper ratio of the tapered pile can be determined to carry the maximum axial load.